In the name of Edmund Husserl: the Gadamer affair or the stairway to emptiness (2011)
The thesis I’m looking to advance is related to Wittgestein’s “Stairway to emptiness”, applied to the intellectual relationship between Edmund Husserl and Hans-Georg Gadamer. An event that is not self evident if we consider that in philosophical discussio